The impact of digital tools and the expected digital transformation in radiotherapy on Dutch radiation therapists (RTTs) - Thijs Ackermans; Paul Cremers; Janne Dingemans; Carol Ou; Marcel Verheij; Maria Jacobs (Technical Innovations & Patient Support in Radiation Oncology)
Background and Purpose: Technological advancements have the potential to mitigate RTT shortages, burnout levels, and turnover rates. However, it is unclear if RTTs currently experience technostress (stress or anxiety from being overwhelmed by technology) and how extensive digital tool usage impacts key job performance indicators (e.g., job engagement, satisfaction, and turnover intentions). This study investigates the impact of digital tools used and expected digital transformation on RTTs’ technostress and key job performance indicators. Materials and Methods: A survey was distributed to RTTs across all Dutch radiotherapy centers, resulting in 265 respondents. The survey included validated questionnaires on digital tool use, technostress, job autonomy, innovative work behavior and job performance indicators. Relationships were assessed using linear regression models and paired samples T-tests (p < 0.05). Results: The number of digital tools used had no significant effect (p < 0.05) on key job performance indicators and was not related to technostress. Technostress negatively impacted key job performance indicators, but explained less than 7 % of the variance. Other factors, such as job autonomy, had a greater influence. When presented with a description of the future perspective of their job role after the expected digital transformation, RTTs reported small declines in key job performance indicators. Conclusion: Current RTT performance is not affected by the number of digital tools used, as RTTs are used to working with digital tools. RTTs showed no technostress. After the predicted digital transformation RTTs remained satisfied and engaged. Ensuring RTTs feel skilled and empowered with decision-making authority is crucial before introducing new digital tools.